Sources of health financing and health outcomes: A panel data analysis - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2018)
We study the differential impacts of public and private sources of health spending on health outcomes using a triple difference approach. We find that private health spending has on average a higher health-promoting effect than public health spending. This result is robust with respect to the choice of outcome measure and covariates in the regression and driven primarily by the countries with ineffective governments. Once we restrict our sample to countries with effective governments, private health spending is no better than public health spending for improving the health outcome.